Study on the seed metering performance of potato seed metering device with three claw type on DEM - Yuhuan Sun; Erhao Chen; Linrong Shi (Journal of Agricultural Engineering)
To address the issues of high seed replay rate and seed missing rate in the existing potato seed metering device, a potato seed metering device with three claw-type designs was developed. Based on discrete element method (DEM) simulation model, the influence of seed-picking claw and seed cleaning plate on the seed metering process was analyzed. A simulation experiment was conducted with lateral spacing, vertical spacing, and terminal radian of the seed-picking claw as factors and the qualification rate as indicator. The influence of relevant factors on seed picking performance was analyzed, and the optimal solution of seed picking claws was obtained. The qualification rate is 89.93% when the lateral spacing is 29.92 mm, the vertical spacing is 1 5mm, and the terminal radian was 29.25°. Moreover, a single-factor experiment was conducted with the angle of the seed cleaning plate as the factor and the qualification rate and seed missing rate as the indicators. The results showed that when the angle of the seed cleaning plate is 7.53°, the qualification rate is 90.1%, and the seed missing rate is 3.7%. In addition, an orthogonal experiment was carried out with seed picking speed, different types of seed picking claw, and the angle of seed cleaning plate as factors, and the seed replaying rate and the seed missing rate as indicators, and the results were experimented on the bench, and the seed replaying rate was 2.7%, and the missing seeding rate was 1.9%.